Penegakan Hukum Pidana Internasional dalam Kejahatan Perang terhadap Kemanusiaan - Fadil Muhammad; Luh Putu Sudini; I Nyoman Sujana (Jurnal Preferensi Hukum, 2020)
War is a condition in which one party subdues its opponent to fulfill his will, a physical or non-physical act between two or more human groups to dominate. The formulation of the problem of this research is how the role of International Criminal Law on law enforcement in war crimes against humanity and how the state responsibility in war crimes against humanity in International Criminal Law. This research method uses the type of normative legal research by doing the assessment based on legal materials of the literature and is a process to find the rule of law, legal principles, and legal doctrines to answer the legal issues faced. War crimes and crimes against humanity are two types of international crimes that exist in twenty international criminal types designed by ILC (International Law Commission) to design the establishment of an international criminal tribunal. The conclusion of this study is the role of International Criminal Law in war crimes against humanity can be concluded that is contained in conventions contained in International Humanitarian Law contains only command or prohibition only but international criminal law have role in giving criminal sanction against violation of command or prohibition that and the state's responsibility in international criminal law can be an obligation to prosecute international criminal offenders encountered in various instruments of International Law. The form of state responsibility under the Rome Statute is that States Parties shall have two main obligations: States Parties shall bring each perpetrator of genocide, crimes against humanity, criminal acts of war and criminal acts of aggression before the courts and the participating States in imposing their jurisdiction in enforcement of International Criminal Law must cooperate fully in the enforcement of International Criminal Law.